The conditional effect of culture on the relationship between ifrs adoption strategies and earnings management - Alhammad, Abdullah; Atqa, Asna Abdullah; Latiff, Ahmed Razman Abdul; Azman-Saini, W. N. W. (Society for Alliance, Fidelity and Advancement (SAFA), 2020)
The purpose of this paper is to investigate the relationship between IFRS adoption strategies and earnings management and examine the conditional effect of culture on this link. The research was based on a sample of firms located in 35 developed and developing countries. The empirical results provided a strong evidence that there was a relationship between IFRS adoption strategies and earnings management. IFRS adoption strategies had substantial negative effects on earnings management and the relationship between them varied according to uncertainty avoidance and power distance. This study is considered important, innovative and useful for regulators and investors as it guides them to develop policies to improve accounting quality.